2005
DOI: 10.1602/neurorx.2.2.237
|View full text |Cite
|
Sign up to set email alerts
|

Single-photon emission computed tomography in neurotherapeutics

Abstract: Summary:The measurement of regional cerebral blood flow (rCBF) by single-photon emission computed tomography (SPECT) is a powerful clinical and research tool. There are several clinical applications now documented, a substantial number under active investigation, and a larger number yet to be studied. Standards regarding patient imaging environment and image presentation are becoming established. This article reviews key aspects of SPECT functional brain imaging in clinical practice, with a particular emphasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[13] It is not indicated in most of the patients with epilepsy but has an important role in presurgical evaluation of refractory epilepsy patients. The use of SPECT in epilepsy stems from the known association of seizures with increased ictal regional cerebral perfusion or interictal decrease in perfusion.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…[13] It is not indicated in most of the patients with epilepsy but has an important role in presurgical evaluation of refractory epilepsy patients. The use of SPECT in epilepsy stems from the known association of seizures with increased ictal regional cerebral perfusion or interictal decrease in perfusion.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Single photon emission computerized tomography (SPECT) is a nuclear medicine imaging method that allows for the quantitative and qualitative evaluation of regional cerebral perfusion. [ 13 ] It is not indicated in most of the patients with epilepsy but has an important role in presurgical evaluation of refractory epilepsy patients. The use of SPECT in epilepsy stems from the known association of seizures with increased ictal regional cerebral perfusion or interictal decrease in perfusion.…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…There are numerous publications proving SPECT functional brain imaging as a powerful research tool, especially in the fields of cerebrovascular disease and cognitive disorders, and there is extensive development in receptor and molecular imaging ( 91 ). In a recent systematic review, Raji et al concluded that SPECT imaging could be useful in evaluating patients with neurological and psychiatrically sequela after TBI ( 92 ).…”
Section: Positron Emission Tomographymentioning
confidence: 99%
“…Radiopharmaceuticals that bind to apoptotic cells (e.g., 99m Tc-Annexin) have been used preclinically to validate the possible toxicity effects in developing therapies [ 97 ]. Other examples on secondary response to the administration of a candidate drug in preclinical models include measurements in blood flow changes [ 98 ] and infiltration of inflammatory cells [ 99 ].…”
Section: Spect In Preclinical Applicationsmentioning
confidence: 99%